Synthetic Approaches for Pyranoquinolines: A Concise Review - Arboleda, Angie D.; Moreno, Leydi M.; Abonia, Rodrigo (Current Organic Chemistry, 2024)
The pyranoquinoline frameworks have a wide distribution in natural products and have displayed a great amplitude of biological activities, attracting the attention of synthetic and medicinal chemists due to their usefulness in agrochemical and pharmaceutical industries. Among the twenty possible isomeric pyranoquinoline frameworks, research reports for only six of them that were found during the period of time covered in this review article (i.e. 2000 to 2023). According to the literature reports during this frame of time, the synthesis of pyranoquinoline derivatives was achieved by following three general synthetic approaches [i.e. (i) via multicomponent cyclizations (MCC), (ii) via bimolecular cyclizations (BMC) and via intramolecular cyclizations (IMC)], mediated by catalyst-free conditions or by diverse environmentally friendly catalysts, in which mechanistic proposal was discussed for several of such processes. Additionally, various obtained pyranoquinoline derivatives reported in this review were subjected to diverse biological evaluations, such as Parkinson´s and Alzheimer´s diseases, as antibacterials, antifungals, and anticancer drugs, among others, indicating the promising biological potential of this class of heterocyclic structure.
Keywords: multicomponent cyclization